If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -11 = 66 Reorder the terms: -11 + n = 66 Solving -11 + n = 66 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + n = 66 + 11 Combine like terms: -11 + 11 = 0 0 + n = 66 + 11 n = 66 + 11 Combine like terms: 66 + 11 = 77 n = 77 Simplifying n = 77
| 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 | | v-52=29 | | 2(6x-10)=31-3(5-3x) | | -24x+-6+7x+9x-27=4 | | p-6=43 | | h*7=15 | | -3x^2+36x-33=0 | | a^2-10+9a=0 | | 9(2x-3)=27 | | 6x+29=-4x-1 | | 7x=9+-3(x+1) | | 3y+y=-40 | | -3(1-n)=6-6n | | 10(v+2)-4v=3(2v+1)-12 | | 17-5(-7-8)+1= | | b-34=11 | | 6x+29=-4x | | 500+35g=55h | | w+-30=-52 | | 34=y-18 | | 7y=-98 | | b+13=42 | | -56=74+10x | | -3(2x-2)=24 | | 8t-10-2t=-6+10+9t | | 6y+3x=22 | | x+10(x+1)+5=550 | | 2y+4x=12.50 | | a^2+6a=7 | | -(5-3x)+x=4 |